Islamic Republic of Afghanistan : First Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria-Press Release; and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Afghanistan's First Review under the Extended Credit Facility (ECF) Arrangement and the Request for Modification of Performance Criteria (PCs). Program implementation has been satisfactory. All quantitative PCs and indicative targets were met. The authorities are planning to contract a limited amount of nonconcessional debt to finance an important infrastructure project and are seeking approval of a modification of the relevant PCs. They are also requesting modification of three PCs for June 2017. These were revised owing to updates of the macroeconomic framework and changes in methodology affecting monetary variables. The IMF staff supports completion of the first review under the ECF arrangement and the authorities' request for a modification of PCs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet